Evidence of a role for GTP cyclohydrolase‐1 in visceral pain. Issue 5 (17th March 2015) - Bulmer, D. C.; Botha, C. A.; Wheeldon, A.; Grey, K.; Mein, C. A.; Lee, K.; Knowles, C. H.; Winchester, W. J.; Aziz, Q.
Abstract: Background: The enzyme guanosine triphosphate‐cyclohydrolase‐1 (GCH‐1) is a rate limiting step in the de novo synthesis of tetrahydrobiopterin (BH4) a co‐factor in monoamine synthesis and nitric oxide production. GCH‐1 is strongly implicated in chronic pain based on data generated using the selective GCH‐1 inhibitor 2, 4‐diamino‐6‐hydroxypyrimidine (DAHP), and studies which have identified a pain protective GCH‐1 haplotype associated with lower BH4 production and reduced pain. Methods: To investigate the role for GCH‐1 in visceral pain we examined the effects of DAHP on pain behaviors elicited by colorectal injection of mustard oil in rats, and the pain protective GCH‐1 haplotype in healthy volunteers characterized by esophageal pain sensitivity before and after acid injury, and assessed using depression and anxiety questionnaires. Key Results: In rodents pretreatment with DAHP produced a substantial dose related inhibition of pain behaviors from 10 to 180 mg/kg i.p. ( p < 0.01 to 0.001). In healthy volunteers, no association was seen between the pain protective GCH‐1 haplotype and the development of hypersensitivity following injury. However, a substantial increase in baseline pain thresholds was seen between first and second visits (26.6 ± 6.2 mA) in subjects who sensitized to esophageal injury and possessed the pain protective GCH‐1 haplotype compared with all other groups ( p < 0.05). Furthermore the same subjects who sensitized to acid and possessed the haplotype, also had significantly lower depression scores ( p < 0.05). Conclusions & Inferences: The data generated indicate that GCH‐1 plays a role in visceral pain processing that requires more detailed investigation. Abstract : View the podcast on this paper at the following sites: Youtube:https://www.youtube.com/watch?v=COHOrt7lu1I iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility/id981449532y In the present study, we demonstrate that pretreatment with the GCH‐1 inhibitor DAHP reduces visceral pain behavior in a rodent model of acute inflammatory visceral pain. Additionally in human studies we demonstrate that the presence of the pain protective GCH‐1 haplotype is associated with lower depression scores and increased pain thresholds following repeat esophageal pain testing in subjects who develop central sensitization to esophageal acidification. Our data indicate that GCH‐1 plays an important role in visceral pain processing that requires more detailed investigation.